Gender Stereotypes and Bias as Depicted in STEM Textbooks of School Education: Insight from Systematic Literature Review - Nandi, Ankur; Hader, Tarini; Das, Tapash (International Journal of Educational Innovation and Research, 2025)
STEM education is vital for fostering creativity and critical thinking among students. Researching gender bias in STEM textbooks is crucial as these materials significantly influence students’ perceptions of gender roles, career aspirations, and cultural beliefs, potentially perpetuating inequalities in STEM fields. This review paper examines five aspects of gender portrayal in STEM textbooks: (i) language and terminology, (ii) visual representation, (iii) professional and occupational roles, (iv) games and leisure activities, and (v) cultural and regional differences. Employing a Systematic Literature Review (SLR) methodology, the study analyzed 39 selected papers from databases like Web of Science, Scopus, Springer Link, Google Scholar, Semantic Scholar, and ERIC, spanning 2004 to 2024. The findings highlight a dominant male presence in leadership roles and adventurous activities, while females are underrepresented or confined to passive and domestic settings. Female achievements are often minimized across cultures and regions. These insights offer valuable guidance for textbook developers, authors, and educators to design gender-sensitive curricula and educational materials. Future research could explore the long-term impact of such biases on students’ career choices and societal attitudes.